Analisis Buku Al-arabiyah lil Jami' Jilid I Sebagai Sumber Pembelajaran Matrikulasi Bahasa Arab di UIN Raden Intan Lampung - Ahmad Ramadhan Wirakarta; Dedy Irawan; Erlina; Syarifudin Basyar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study was motivated by the use of the book Al-‘Arabiyah lil Jāmi’ Volume I in the Arabic language matriculation program at UIN Raden Intan Lampung, which is not yet fully suited to the needs of new students with varying levels of initial proficiency. This study aims to analyze the suitability of the book based on four aspects of BSNP assessment, namely content, language, presentation, and graphics. The research method used a qualitative descriptive approach through content analysis with documentation techniques on the material structure, language characteristics, and chapter presentation. The results of the study indicate that this book is suitable for use as a matriculation learning resource; the material is arranged in a logical sequence, the language is easy for beginners to understand, and the graphic design is quite supportive. However, several shortcomings were found in the presentation aspect, such as the absence of chapter summaries, a glossary, and references, as well as illustrations that are not accompanied by explanations. Overall, this book is relevant for use, but it needs improvement to better meet the standards of an ideal textbook.